Cilia and their role in neural tube development and defects. Issue 2 (June 2022) - Yan, Lu; Zheng, Yu-Fang
Abstract : Abstract: Cilia are microtubule-based filamentous organelles that play a vital role in embryogenesis. Multiple signal transduction pathways are orchestrated by cilia, such as Hedgehog and planar cell polarity signals. Various studies, spanning over last 2 decades, have emphasized the role of cilia-mediated signaling cascades in regulating neural tube patterning and development. Moreover, the deficiency of certain ciliary genes have been reported to cause neural tube defects (NTDs), which are a set of disorders that occur due to perturbation of normal neural tube closure. However, the mechanisms underlying cilia dysfunction resulting NTDs remain unclear. Recent studies have highlighted the association of phosphoinositide signaling with cilia, thereby conferring novel insights into the function of cilia during neural tube development. Here, we have reviewed recent studies on cilia, focusing on the molecular mechanism underlying the involvement of cilia in neural tube development and the role of ciliary disruption in the development of NTDs.